2000
DOI: 10.1021/jp0030544
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Force Microscopy and Near-Field Scanning Optical Microscopy Measurements of Single Human Retinal Lipofuscin Granules

Abstract: Novel high-resolution microscopic techniques have been utilized to characterize the spatial distribution of orange emitting fluorophores, e.g., A2E, in lipofuscin granules isolated from human retinal pigment epithelium cells. Granules have been imaged using atomic force microscopy (AFM) and near-field scanning optical microscopy (NSOM). Near-field scanning optical microscopy images of lipofuscin show that the orange fluorophores, including A2E, are not major components of the granule. These results suggest tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 17 publications
4
17
0
Order By: Relevance
“…Prior studies have shown that the emission across a single LF granule is invariant with respect to the Ϸ150-nm resolution limit of near-field scanning optical microscopy (NSOM). Significant variation in the emission maxima and spectral shape from different individual LF granules was observed by using both NSOM and spectrally resolved confocal microscopy (52,53). The variation in the emission maxima observed in the present study is shown in Table 1.…”
Section: Emission Behavior Of Individual Lipofuscin Granulessupporting
confidence: 59%
See 1 more Smart Citation
“…Prior studies have shown that the emission across a single LF granule is invariant with respect to the Ϸ150-nm resolution limit of near-field scanning optical microscopy (NSOM). Significant variation in the emission maxima and spectral shape from different individual LF granules was observed by using both NSOM and spectrally resolved confocal microscopy (52,53). The variation in the emission maxima observed in the present study is shown in Table 1.…”
Section: Emission Behavior Of Individual Lipofuscin Granulessupporting
confidence: 59%
“…The emission spectra of 91 granules were collected and analyzed. As previously reported, significant variations in the emission maxima were observed (52,53). Prior studies have shown that the emission across a single LF granule is invariant with respect to the Ϸ150-nm resolution limit of near-field scanning optical microscopy (NSOM).…”
Section: Emission Behavior Of Individual Lipofuscin Granulessupporting
confidence: 57%
“…Such shape and characteristic sizes were typical of all lipofuscin granules studied. A similar shape of the granules was also described in [7]. Figure 1b shows the image obtained during scanning of the central region of the granule by means of phase contrast.…”
Section: Methodssupporting
confidence: 70%
“…The lipofuscin of RPE is amassed within organelles of the lysosomal compartment of the cells; because of their ultrastructural appearance, these bodies are known as lipofuscin granules (49)(50)(51)(52). Other macromolecules phagocytosed by the RPE are degraded by lysosomal enzymes to small molecules that leave the lysosome assisted by permeases ( 53 ).…”
Section: All-trans -Retinal and Phospholipidmentioning
confidence: 99%